VISUALISASI MESIN HASRAT PADA IKLAN OLATTE MELALUI PENDEKATAN SEMIOTIKA - Akmal Pijar Aradhana; Guruh Ramdani; Nathaniela Anya Jeconia Manoppo; Muhammad Fadlhy Fajarsyach; Jinanti Audiza; Muhamad Aditya Nursyahbani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
This study is motivated by the importance of understanding the role of visual elements in building consumer desire through advertisements, particularly in the case of Olatte pear-flavored beverage. In a consumerist society, desire does not arise naturally but is constructed through media and visual symbols. This research employs a descriptive qualitative method with Charles Sanders Peirce's semiotic approach, combined with literature study as the data collection technique. The findings reveal that visual elements in the Olatte advertisement—such as water, chili, and pear—function as icons, indexes, and symbols that construct meaning and stimulate consumers' desire to purchase the product. The advertisement strategically employs the concept of the